Youth Perception on Agricultural Sector (Case Study in Watukenongo, Pungging, Mojokerto). - Dio Bagus Setiawan; Jabal Tarik Ibrahim; Nur Ocvanny Amir (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
This study aims at analyzing youth perceptions on agricultural sector and analyzing factors affecting youth perceptions on agricultural sector in Watukenongo village. 91 respondents were involved in this study as sample. Simple random sampling technique was employed in this study. All respondents are youths in Watukenongo village, Pungging, Mojokerto Regency. For data analysis method, the SEM-PLS (Partial Least Square) technique with the help of WarpPLS 7.0 software was implemented. The results showed that the youth perception on agricultural sector was poor in terms of enthusiasm in doing or continuing to farm; it was good in terms of income satisfaction resulted from farming and in terms of self-ability in cultivating agricultural land; and it was very good in terms of pleasure in doing farming activities. The obtained value of R-square is 0.690. The factors affecting youth perception agricultural sector were (1) income, (2) land, and (3) education. Meanwhile, social status and age did not have a significant effect.